<An> Exploratory study of a comparison between the UK and Czech Republic of the financial models used in the appraisal of ICT and NON-ICT capital projects - Hynek, Josef
Porovnanie modelov hodnotenia ICT a NON-ICT investičných projektov vo Veľkej Británii a v Českej republike. Model PB (Payback period), DPB model (Discounted payback model), ARR model (Accounting rate of return), model NPV (Net present value), model IRR (Internal rate of return), model MIRR (Modified internal rate of return).